Central nervous system involvement in anaplastic large cell lymphoma in childhood: Results from a multicentre European and Japanese study. Issue 10 (29th May 2013) - Williams, Denise; Mori, Tetsuya; Reiter, Alfred; Woessman, Wilhelm; Rosolen, Angelo; Wrobel, Grazyna; Zsiros, Jozsef; Uyttebroeck, Anne; Marky, Ildiko; Le Deley, Marie‐Cécile; Brugières, Laurence
Abstract In an international study of systemic childhood ALCL, 12/463 patients had CNS involvement, three of which had isolated CNS disease. Comparative analysis of CNS positive and negative patients showed no difference in ALK positivity, immunophenotype, presence of B symptoms or other sites of disease. The lymphohistiocytic variant was over represented in the CNS positive group (36% vs. 5%). With multi‐agent chemotherapy, including high dose methotrexate, Ara‐C and intrathecal treatment, the event free and overall survival of the CNS positive group at 5 years were 50% (95%CI, 25–75%) and 74% (45–91%), respectively with a median follow up of 4.1 years. Pediatr Blood Cancer 2013;60:E118–E121. © 2013 Wiley Periodicals, Inc.